Obtenção e caracterização de microencapsulados de caseinatos carregados com extrato de própolis vermelha - Almeida, Clinston Paulino de (2017)
The propolis is a resinous substance, chemically complex and rich in secondary metabolites that confer it to a vast therapeutic application against the activities, such as: the antimicrobial, antioxidant, anticariogenic, anti-inflammatory, and that when it associated to foods, it confers them to the functional character. However, its application becomes limited because of its characteristics, such as the low solubility and the unpleasant astringency, being therefore necessary the use of mechanisms that are capable of reverting and improving these undesirable characteristics. Due to this, the pharmaceutical and food industries take hold of the processes that seek to beneficiate and offer products enriched with propolis that meet the demand and the necessity of their applications. An alternative for the beneficiation of the propolis is the application of a microencapsulation technique in spray-drying, which consists in incorporating the bioactive into a matrix that is capable of conferring to the encapsulated material to the industrially desirable characteristics for the bioproduct. The various forms of caseins have been applied as an encapsulating agent, this happens because of its physico-chemically favorable structure within the various biological systems. Thus, this work had as objective to obtain and characterize caseinates, and sought to develop microparticles for the therapeutic or functional applicability. After forming the casein-propolis solution, the drying was carried out in a spray-dryer following pre-established parameters. In the characterization stage, physico-chemical techniques (particle size, zeta potential, FTIR, TGA and DTA) were applied. The microparticle morphology was observed by SEM and the integrity of the protein in the final product (propolis-casein complex) was seen with the help of acrylamide gel through the electrophoresis technique. The antioxidant activity was measured by connecting it to the radical DPPH and the antimicrobial activity was evaluated for the growth inhibition of the Pseudomonas aeruginosa and Staphylococcus aureus strains. The complex was formed and submitted to a study of dissolution in different media (reverse osmosis water and phosphate buffer pH 7.4) and agitation at 100 and 150 rpm. With the physicochemical characterization; it was possible to identify, through spectroscopy in the infrared and thermal analysis (TGA and DTA), the interaction between casein-propolis and the formation of the microparticles that showed a population of micrometric particles (1186nm - 5463nm) and a sub-micrometric population (72nm - 715nm), proving to be stable when they are in a solution with a zeta potential between -33.0 and -41.9 mV. The SEM reveals spherical particles with no apparent porosity or formation of agglomerates. The electrophoresis revealed typical casein bands confirming the non-degradation of the protein through the drying. The antioxidant capacity was higher than 50%. Inhibition halos presented between 8 to 24 mm in the microbiological test through disc diffusion and in agar medium the compositions. In the dissolution profile, it showed to be a highly soluble complex in water with immediate release, mainly in a pH 7.4 phosphate buffer medium and reverse osmosis water.